Synthesis and Evaluation of the Anti-Oxidant Capacity of Curcumin Glucuronides, the Major Curcumin Metabolites - Ambar K. Choudhury; Suganya Raja; Sanjata Mahapatra; Kalyanam Nagabhushanam; Muhammed Majeed (Antioxidants, 2015)
Curcumin metabolites namely curcumin monoglucuronide and curcumin diglucuronide were synthesized using an alternative synthetic approach. The anti-oxidant potential of these curcumin glucuronides was compared with that of curcumin using DPPH scavenging method and Oxygen Radical Absorbance Capacity (ORAC) assay. The results show that curcumin monoglucuronide exhibits 10 fold less anti-oxidant activity (DPPH method) and the anti-oxidant capacity of curcumin diglucuronide is highly attenuated compared to the anti-oxidant activity of curcumin.